An Fmoc-compatible method for synthesis of peptides containing photocaged aspartic acid or glutamic acid. Issue 31 (29th July 2015) - Tang, Shan; Cheng, Jing-Yuan; Zheng, Ji-Shen
Graphical abstract: Abstract: A new method compatible with 9-fluorenylmethoxycarbonyl (Fmoc) solid phase peptide synthesis (SPPS) was developed to synthesize photocaged peptides carrying the photosensitive 4-methoxy-7-nitroindoline (MNI) group on the side chain of aspartic acid (Asp) and glutamic acid (Glu). The caged building blocks, Fmoc-Asp(MNI)-OH and Fmoc-Glu(MNI)-OH, could be readily synthesized on multi-gram scale. An important advantage of the new method is that the MNI group prevents the formation of aminosuccinyl side products and pyrrolidones during Fmoc SPPS and has rapid photolysis kinetics. Thus our method provides a useful approach for photocaging of peptides and proteins at side chain carboxylic groups.